IMPACT OF SOCIAL PROTECTION PROGRAMMES ON HOUSEHOLD ACCESS TO HEALTHCARE SERVICES IN NASARAWA STATE - AYAKA, MATHEW AYUBA; ILEMONA , ADOFU; UGWUOKE, WALTER OKWUDILI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The paper examined the impact of social protection programmes on household access to healthcare services in Nasarawa State. Primary data was used for the study, which was collected with the aid of survey instrument (questionnaire). A sample of 439 treatment group and same number of sample of the control group were considered in the research. The study adopted a quasi-experimental design and Difference-in-Difference regression model was employed for the data analysis. Results of analysis of the three outcome variables were statistically significant for all components of the social protection programmes (Conditional Cash Transfer, Health Insurance, and N-Power), implying that social protection programmes significantly increased household access to healthcare services in Nasarawa State. The study concluded that social protection programmes are veritable instruments of addressing health inequalities and affordability of healthcare services, and if properly harnessed will lead to achieving the Sustainable Development Goal three in Nasarawa State. The paper based on the findings recommended that more awareness is required on social protection programmes operations in the Nasarawa State, and there is need for institutionalization of social protection policy in Nasarawa State for effective service delivery.